Landscape signatures and seabed characterization in the marine environment of north-west Qatar (poster) - al-Naimi, Faisal; Cuttler, Richard; Alhaidous, Ibrahim Ismail; Dingwall, Lucie; Momber, Garry; al-Naimi, Sadd; Breeze, Paul; al-Kawari, Ahmed Ali (Proceedings of the Seminar for Arabian Studies, 2012)
The Arabian Gulf is a fairly shallow sea and during the Last Glacial Maximum was an open landscape that may have formed refugia for human groups. The discovery of archaeological remains predating 8000 years ago in the marine areas of the North Sea and the English Channel would suggest that the Arabian Gulf also has a similar potential for the favourable survival of premarine transgression deposits. In addition, the Gulf has been part of a maritime trade network, which extends back to the seventh millennium, and therefore the region has the potential for shipwrecks from both the historic and prehistoric periods. Despite this, however, very little maritime archaeological research directed towards the discovery of such remains has been undertaken. Given the expense and logistical issues associated with diving and underwater survey this may not be entirely surprising. To survey the marine areas of Qatar alone using a team of divers would take many years, particularly given strong regional currents and limited visibility. In recent years the rapid development of geophysics has provided new opportunities to investigate wider areas of the marine landscape and to develop strategies for targeted diver inspections of geophysical anomalies. The analysis of a large tract of geophysical data off the north-west coast of Qatar revealed more than eighty anomalies with a seabed expression, some of which were clearly modern and others that were considered to have reasonable archaeological potential. Of the anomalies subject to subsequent diver inspection, none proved to be of archaeological interest. The visual inspection of geophysical anomalies is, however, providing valuable regional baseline data for the interpretation of anthropogenic marine signatures. The clarification of signatures from different types of anomalies enables the calibration of regionally important geophysical data. In addition, these inspections have significantly increased our understanding of the seabed characteristics around north-eastern Qatar. Future geophysical surveys will be focused not simply on anomalies but on characterizing the submerged landscape using higher-resolution geophysical data from a range of sensors.